Biophysical variables in fertile islands of the Argentinian Arid Chaco - Karlin, Marcos Sebastián (2020)
Ponencia presentada en International Scientific Conference. Dryland Ecosystems: Threats and oportunities associated with climate change. Piura, Perú, 3 al 7 de marzo de 2020.